Standarisasi Spesifik dan Non Spesifik dari Ekstrak Etanol Daun Beluntas (Pluchea indica L. Less.) - Wijaya, Sumi; Setiawan, Henry Kurnia; Ano, Lucyanna Ayu Lestari (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2017)
Indian fleabane (Pluchea indica (L.) Less.), on of the species in Asteraceae family, is widely used for traditional medicine. A standardization process is needed as an effort to improve the quality and safety of products, so that it is expected to increase the trust in drugs derived from natural ingredients. This study aims to determine the morphology and anatomy of Indian fleabane leaves and to determine the standardization value of the ethanol extract of Indian fleabane leaves. Dried powder of Indian fleabane leaves are obtained from three different regions (Bogor, Malang and Surabaya). The extract was obtained by maceration method using 96% ethanol as a solvent. Specific standardization includes identity, macroscopic, determination of soluble extract, phytochemical screening, TLC (Thin Layer Chromatography) pattern determination, determination of infrared spectrum profile, determination of UV-Vis spectrum profile, and determination of flavonoid, phenol and alkaloid total content. Nonspecific standardization includes determination of total ash content, water soluble ash content, acid insoluble ash content, drying losses, specific gravity and pH. Organoleptic observations showed the ethanol extract of Indian fleabane leaves has blackish brown and aromatic odour. The mobile phase being used for TLC profile chromatogram was n-hexane: ethyl acetate (7: 3). Based on the results, the screening results of Indian fleabane contain alkaloids, flavonoids, polyphenols, tannins, saponins, steroids and triterpenoids. The Infra red spectrophotometer analysis showed the range of wave numbers of 2924 - 2925, 1515 - 1516, 1259 - 1260, 1159 - 1162, 1112 - 1115, 1046 - 1048, 811 - 812, 505 - 506 and 452 - 454 cm- 1. The standardization value of Indian fleabane ethanol extract showed ethanol soluble extract> 65%, water soluble extract> 49%, water content